Virtual modelling of novel applicator prototypes for cervical cancer brachytherapy - Petrič, Primož (Radiology and oncology (Ljubljana), 2016)
Standard applicators for cervical cancer Brachytherapy (BT) do not always achieve acceptable balance between target volume and normal tissue irradiation. We aimed to develop an innovative method of Targetvolume Density Mapping (TDM) for modelling of novel applicator prototypes with optimal coverage characteristics. Patients and methods. Development of Contour-Analysis Tool 2 (CAT-2) software for TDM generation was the core priority of our task group. Main requests regarding software functionalities were formulated and guided the coding process. Software validation and accuracy check was performed using phantom objects. Concepts and terms for standardized workflow of TDM post-processing and applicator development were introduced. Results. CAT-2 enables applicator-based co-registration of Digital Imaging and Communications in Medicine (DICOM) structures from a sample of cases, generating a TDM with pooled contours in applicator-eye-view. Each TDM voxel is assigned a value, corresponding to the number of target contours encompassing that voxel. Values are converted to grey levels and transformed to DICOM image, which is transported to the treatment planning system. Iso-density contours (IDC) are generated as lines, connecting voxels with same grey levels. Residual Volume at Risk (RVR) is created for each IDC as potential volume that could contain organs at risk. Finally, standard and prototype applicators are applied on the TDM and virtual dose planning is performed. Dose volume histogram (DVH) parameters are recorded for individual IDC and RVR delineations and characteristic curves generated. Optimal applicator configuration is determined in an iterative manner based on comparison of characteristic curves, virtual implant complexities and isodose distributions. Conclusions. Using the TDM approach, virtual applicator prototypes capable of conformal coverage of any target volume, can be modelled. Further systematic assessment, including studies on clinical feasibility, safety and effectiveness are needed before routine use of novel prototypes can be considered.
Keywords: aplikatorji; applicators; brachytherapy; brahiterapija; cervical cancer; maternični vrat; rak (medicina); virtual modelling